Implementation of Federalism in Nepal: The Devil is in the Detail (Lex Scientia Law Review, 2022)
After a long period of instability, Nepal adopted a new Constitution in 2015, creating a multiparty federal republic. Previously Nepal had been a unitary state, albeit with a long period of political instability and insurgencies. In 2017 the two competing communist parties merged to form the ruling Nepal Communist Party (NCP), which operated with a 2/3rd majority in the House of Representatives. The implementation of federalism has been slow and uneven. Despite assurances to the contrary, the government’s response to the COVID-19 pandemic has been lacking, with Constitutional obligations ignored. The machinations of the then Prime Minister have exacerbated this, apparently supported by the President to overcome constitutional norms to keep the Prime Minister in power. The paper analyses the devolution of powers to the provincial and local levels described in the constitution. There have been successes and failures. There appeared to be a concerted effort from the federal parliament and some in the bureaucracy to continue to centralize power. This early inaction has hindered its response to the pandemic. Of even more concern is the then prime minister's role as he sought to maintain his hold on power by ignoring the provisions of the Constitution.